2021
DOI: 10.3390/su13137231
|View full text |Cite
|
Sign up to set email alerts
|

Democratically Sustainable Local Development? The Outcomes of Mixed Deliberation on a Municipal Merger on Participants’ Social Trust, Political Trust, and Political Efficacy

Abstract: Municipal mergers are typically contentious and polarizing issues among both citizens and politicians. In deciding on these, municipal-level referendums are often commissioned by municipal councils. Referendums, though, are also per se polarizing processes that only exacerbate an already polarizing issue. Adding deliberation to referendum processes has been shown in previous studies to be a more democratically sustainable process than mere referendums. In this study, we explore the use of mixed deliberation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Some previous studies have reported mixed or negative findings of politicians' involvement in deliberation on an equal footing with ordinary citizens. Strandberg et al (2021) observed no changes in citizens' trust and efficacy when local politicians and citizens deliberated together on a highly polarised topic of a municipal merger. In the United States, online town hall meetings were accompanied by a process in which citizens could pose questions and comments to members of the congress, who then responded (Minozzi et al, 2015; Neblo et al, 2018).…”
Section: Case Studies Of Politician and Citizen Participation In Mini...mentioning
confidence: 99%
“…Some previous studies have reported mixed or negative findings of politicians' involvement in deliberation on an equal footing with ordinary citizens. Strandberg et al (2021) observed no changes in citizens' trust and efficacy when local politicians and citizens deliberated together on a highly polarised topic of a municipal merger. In the United States, online town hall meetings were accompanied by a process in which citizens could pose questions and comments to members of the congress, who then responded (Minozzi et al, 2015; Neblo et al, 2018).…”
Section: Case Studies Of Politician and Citizen Participation In Mini...mentioning
confidence: 99%
“…The public views concerning the merger were highly segregated, with the Swedish-speaking majority in Korsholm generally being more critical of the merger plan, and the Finnish-speaking minority having more positive attitudes towards it (Strandberg et al, 2018; Strandberg and Lindell, 2020). The above-mentioned survey shows that the mean opinion was only 3.71 among Swedish speakers, whereas it was 7.38 among Finnish speakers.…”
Section: Context: the Merger Issue In Korsholmmentioning
confidence: 99%
“…The support for the merger was highest in the municipal centre of Smedsby ( M = 6.38), which lies just next to the municipal border with Vaasa. Attitudes became pronouncedly more reserved when moving to the more sparsely populated rural areas and to the archipelago (Strandberg et al, 2018; Strandberg and Lindell, 2020).…”
Section: Context: the Merger Issue In Korsholmmentioning
confidence: 99%
“…Mini-publics are now widely used in policymaking practice as a means of bringing citizens into processes of framing, advising on, or deciding about, complex public policy issues such as climate action and environmental health from local to global governance [3], exemplified by the rise of climate assemblies [1]. A key aim of the mini-publics is to realise norms of deliberative democracy [4] and to foster its long-term sustainability, as argued in this special issue of the journal by Strandberg et al [5], in relation to mixed deliberations between citizens and politicians, and by Kulha et al [6], in relation to environmental intergenerational fairness.…”
Section: Introductionmentioning
confidence: 99%